Thermodynamic performance assessment and application feasibility analysis of small heat pump water heater using CO2/R41 azeotropy mixture as refrigerant for sustainable development - Wang, Dong; Li, Mengxue; Gu, Zhipan; Mei, Shengong; Deng, Sensen; Lu, Yuehong; Yu, Fangwen (Frontiers in Energy Research, 2023)
In order to improve the application possibility of CO2/R41 azeotropy mixture in the refrigeration industry, the optimum mass ratio of composition is defined and determined according to the thermodynamic properties and safety. On the basis of the first and second laws of thermodynamics, a model is proposed to evaluate the performance of CO2/R41 single-stage transcritical cycle (CO2/R41 cycle) in which a throttling valve is integrated and CO2/R41 azeotropy refrigerant is adopted. The performance of CO2/R41 cycle at the optimum mass ratio of CO2/R41 azeotropy mixture is then compared with that of a CO2 two-stage transcritical cycle with throttling valve (CO2 two-stage cycle) and that of a CO2 single-stage transcritical cycle with expander (CO2 expander cycle). The results show that the optimum mass ratio of CO2/R41 azeotropy mixture is 0.583/0.417. Compared with CO2 two-stage cycle and CO2 expander cycle, CO2/R41 cycle has the advantages of a simpler structure, lower optimum high pressure, appropriate discharge temperature of the compressor, and higher COP. Therefore, the CO2/R41 azeotropy mixture with the mass ratio of 0.583/0.417 is eco-friendly and can be considered as a good alternative refrigerant for application in the refrigeration industry. The simple CO2/R41 cycle shows great feasibility to replace the complex CO2 two-stage cycle and CO2 expander cycle.